(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This article discusses the process of developing Indonesian criminal law and how it relates to Islamic crime. The purpose of this study is to know and describe the development of Indonesian criminal law and to analyze its relevance to Islamic crime. This type of writing is library research using data in the form of seconds. which consists of literature on Indonesian crime and Fiqh Jinayah as well as journals related to the issues studied. Data is collected through studies in the library, after the data is collected, the data is processed and conclusions are drawn to produce new observations. Based on the results of the research, it can be concluded that the criminal law provisions in force in Indonesia are a legacy of the Dutch colonialists in the form of the Criminal Code (KUHP). With the development of the times and the increasing complexity of problems related to crime, several laws and regulations have been made as a legal umbrella to resolve all cases that arise. From several criminal provisions there is relevance to Islamic criminal law, such as the death penalty known as qishahsh in Islamic criminal law. Likewise the punishment for thieves in various forms contained in the Criminal Code as a statutory regulation imposed by the government. In Islamic criminal law there is also a punishment for thieves with various provisions, and there is an opportunity for the application of punishment for thieves in a form known as ta’zir.